2019
DOI: 10.1051/0004-6361/201833191
|View full text |Cite
|
Sign up to set email alerts
|

Photoionized emission and absorption features in the high-resolution X-ray spectra of NGC 3783

Abstract: Our Swift monitoring program triggered two joint XMM-Newton, NuSTAR and HST observations on 11 and 21 December 2016 targeting NGC 3783, as its soft X-ray continuum was heavily obscured. Consequently, emission features, including the O vii radiative recombination continuum, stand out above the diminished continuum. We focus on the photoionized emission features in the December 2016 RGS spectra, and compare them to the time-averaged RGS spectrum obtained in 2000-2001 when the continuum was unobscured. A two-phas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 76 publications
(112 reference statements)
4
36
1
Order By: Relevance
“…These spectra are similar to those found in NGC 5548 and NGC 3783 (Kaastra et al 2014;Mao et al 2018Mao et al , 2019, where major obscuration events caused by outflowing absorption cause large flux drops at low energies and reveal the soft X-ray emission lines. In this case, however, the flux drop is intrinsic to the source, and we see the effect of the outflow acting on the emission lines.…”
Section: Discussionsupporting
confidence: 82%
“…These spectra are similar to those found in NGC 5548 and NGC 3783 (Kaastra et al 2014;Mao et al 2018Mao et al , 2019, where major obscuration events caused by outflowing absorption cause large flux drops at low energies and reveal the soft X-ray emission lines. In this case, however, the flux drop is intrinsic to the source, and we see the effect of the outflow acting on the emission lines.…”
Section: Discussionsupporting
confidence: 82%
“…After fitting the two narrow emission components, we detected an excess fit residual in the O vii triplet at 22 Å, which required an additional component. A broad emission component was found to significantly improve the fit to the spectra of NGC 5548 (Mao et al 2018) and NGC 3783 (Mao et al 2019), therefore, a third PION emission component (EM3), coupled with a Gaussian velocity broadening component VGAU (represented by the parameter v b ), was also fitted. The broad component improves the fit by ∆C = 23, reducing the residuals at 22 Å (C = 2450 for 1545 d.o.f.…”
Section: Emissionmentioning
confidence: 99%
“…Mao et al (2018) found two narrow emission components explained this discrepancy as each had a different outflow velocity, with no influence on the geometry. In the case of NGC 3783, adding a broadened emission component significantly improved the fit by ∆C ∼ 200 (Mao et al 2019). For this reason, we applied the same approach to NGC 7469.…”
Section: The O VII Tripletmentioning
confidence: 99%
See 2 more Smart Citations